Finite Element Analysis for Underground Deep Excavation Behavior in Phnom Penh City - Roeun, Daro; Sukkarak, Raksiri; Likitlersuang, Suched (การประชุมวิศวกรรมโยธาแห่งชาติ ครั้งที่ 28, 2023)
Underground space is urgently required to be used in economic imperative for landscape purposes in the Phnom Penh City of Cambodia due to the rapidly increasing economy and population over a few decades. Within the excavation work, lateral wall movement and ground surface settlement are critical concerns for engineers that could be affected the adjacent buildings, roads, etc. In this study, a deep excavation site located in Phnom Penh soft ground is selected to investigate. The 2D and 3D finite element analyses are utilised for predicting deep excavation behaviour, including lateral wall movement and ground surface settlement. The Mohr-Coulomb plasticity model was employed in deep excavation modelling. Empirical equations based on the maximum lateral wall movement and maximum ground surface settlement relationship are used to predict the wall movement and ground settlement profile. Finally, the results from finite element simulations, empirical analysis, and monitoring data are compared and discussed.